IMPLICIT FUNCTION THEOREM AND ITS APPLICATIONS: https://doi.org/10.5281/zenodo.15377846 - Nurmonova , E.U.; Almuratov , F.M. (Journal of International science networks, 2025)
The Implicit Function Theorem is a fundamental result in mathematical analysis with far-reaching implications in differential equations, optimization, and manifold theory. This theorem provides conditions under which a relation defined by an equation can be locally expressed as a function of some variables in terms of others. In this article, we explore the theoretical foundations of the Implicit Function Theorem, its proof, and its applications in various fields, including economics, physics, and engineering. We discuss how the theorem facilitates the study of constrained optimization, implicit differentiation, and the stability of dynamical systems. Additionally, we present illustrative examples to demonstrate its practical utility in solving nonlinear equations and modeling real-world phenomena.